Analysis of Word Choice Errors in Narrative Text Composition of Grade V Students at Giripada State Elementary School - Hasanah, Windatul; Widjojoko, Widjojoko (Educationist: Journal of Educational and Cultural Studies, 2022)
The purpose of this research is (1) To find out what are the aspects of word choice errors in the narrative essays of grade V students at SDN Giripada. (2) To describe the error-prone areas obtained in word selection. The research approach used in this research is a synchronous approach. This research method uses qualitative methods. Data collection techniques using document and sampling methods. The data in this study are all sentences that contain errors in the aspects of inaccuracy, inaccuracy, and incompatibility in narrative text essays for grade V students at SDN Giripada while the source of the data in this study was obtained from narrative text essays from grade V students at SDN Giripada. The results of the study show that in the choice of words in the narrative essays of grade V students at SDN Giripada there are still many mistakes. We can know these errors based on aspects of accuracy, precision, and harmony in the choice of words. The error-prone area from the aspect of inaccuracy is the choice of words used that are not in accordance with what you want to express and are not in accordance with the meaning so that it becomes unacceptable. Like the use of the word clock. Errors from the aspect of inaccuracy are the choice of words used to cause ambiguous sentence meanings and use of non-standard words. Like the use of the word cleaning up. While the error from the aspect of incompatibility is the choice of words used does not lead to conformity of meaning with the context of the existing sentence. As in the use of words give.